THE TECTONO - STRATIGRAPHIC EVOLUTION OF PINDOS FORELAND EAST OF MESOLONGI - Noti, A.; Tserolas, P.; Maravelis, A.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2016)
Sedimetological analysis of submarine fan deposits, both north and south of Evinos River, east of Mesolongi town, showed that there are different sedimentological conditions. The southern part outcropped between Klokova and Varasova Mountains, influenced by Gavrovo thrust activity, is characterized by coarse grained inner fan deposits, and sourced both from Pindos chain and the uplifted Klokova and Varasova Mountains. Gavrovo thrust activity, took place during the sedimentation producing intrabasinal highs, changing basin geometry. In the northern part, where outer fan deposits passes upwards to inner fans, there is no obvious influence of Gavrovo thrust but mostly the influence of internal Ionian Thrust. Between the two studied areas there is a high deformed area, about 1km wide, trending parallel to the Evinos River in a ENE direction, showing that probable Evinos River flows on a strike-slip fault.